Nuclear quantum effects on the vibrational dynamics of liquid water - Ojha, Deepak; Henao, Andres; Kühne, Thomas D. (Journal of Chemical Physics, 2018)
Based on quantum-mechanical path-integral molecular dynamics simulations, the impact of nuclear quantum effects on the vibrational and hydrogen bond dynamics in liquid water is investigated. The instantaneous fluctuations in the frequencies of the O-H stretch modes are calculated using the wavelet method of time-series analysis, while the time scales of the vibrational spectral diffusion are determined from frequency-time correlation functions, joint probability distributions, and the slope of three-pulse photon echo. We find that the inclusion of nuclear quantum effects leads not only to a redshift of the vibrational frequency distribution by around 130 cm-1 but also to an acceleration of the vibrational dynamics by as much as 30%. In addition, quantum fluctuations also entail a significantly faster decay of correlation in the initial diffusive regime, which is in agreement with recent vibrational echo experiments.
CRIS-Team Scopus Importer:2023-03-20